Nurse-computer performance: considerations for the nurse administrator. - Mills ME; Staggers N (Journal of Nursing Administration (JONA), 1994)
Regulatory reporting requirements and economic pressures to create a unified healthcare database are leading to the development of a fully computerized patient record. Nursing staff members will be responsible increasingly for using this technology, yet little is known about the interaction effect of staff characteristics and computer screen design on on-line accuracy and speed. In examining these issues, new considerations are raised for nurse administrators interested in facilitating staff use of clinical information systems.